NANOCON 2019 Conference Proeedings 2020
DOI: 10.37904/nanocon.2019.8569
|View full text |Cite
|
Sign up to set email alerts
|

The Source of the Surface Fluorescence of Nanodiamonds

Abstract: In this paper photoluminescence properties of aqueous suspensions of carbon nanoparticles (nanodiamonds, carbon dots and complexes on their basis) with different ratio of surface carbon in sp 3 -and sp 2 -hybridizations were studied by methods of Raman, fluorescence and IR absorption spectroscopy. It was found that intensity of photoluminescence correlates with amount of carbon in non-diamond phase on the surface of nanoparticles. Nanoparticles with high non-diamond carbon phase content revealed more intense p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The difference in NDs’ PL intensities (of F 0 values) can also be explained by the dependence of the surface PL on the hybridization of surface carbon. In a number of studies, it was suggested that sp 2 -hybridized carbon, not the diamond surface, is the source of the surface PL of NDs. It follows from Figure a that on the surface of all studied NDs there is indeed the sp 2 -hybridized carbon, varying in amount and state (amorphous or graphitelike). Such differences in surface carbon hybridization can contribute to the observed differences in the intensity of NDs’ PL (Figure ).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The difference in NDs’ PL intensities (of F 0 values) can also be explained by the dependence of the surface PL on the hybridization of surface carbon. In a number of studies, it was suggested that sp 2 -hybridized carbon, not the diamond surface, is the source of the surface PL of NDs. It follows from Figure a that on the surface of all studied NDs there is indeed the sp 2 -hybridized carbon, varying in amount and state (amorphous or graphitelike). Such differences in surface carbon hybridization can contribute to the observed differences in the intensity of NDs’ PL (Figure ).…”
Section: Resultsmentioning
confidence: 94%
“…Photoluminescence (PL) of NDs and CDs is also dependent on the properties of nanoparticles’ surfaces and their immediate environment. For NDs, the depednece of PL on their surface chemistry, on the strength of the environments’ hydrogen bonds, ,, and on interactions with biomolecules , allowed us to distinguish the specific type of ND emission:surface photoluminescence, distinct from the well-studied PL of color centers in the diamond core. Recently, increasingly more authors believe that the source of surface PL of nanodiamonds is the functionalized sp 2 -hybridized carbon on their surfaces. …”
Section: Introductionmentioning
confidence: 99%